THE IMPACT OF THE INCREASED SPEED OF TRAINS ON WASTED ENERGY - Korzhenevych, I. P.; Kurgan, M. B.; Barash, Yu. S.; Kurhan, D. M. (Science and Transport Progress, 2008)
Influence of the increase of train speed on the consumption of power resources is under consideration.